„Przeczuwał o wiele późniejszą teorię Hipolita Taine’a…”? Piotr Chmielowski o postawie krytycznoliterackiej Maurycego Mochnackiego - Krysowski, Olaf (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
Piotr Chmielowski considered Maurycy Mochnacki’s attitude in literary criticism as an expression of the 19th-century culture viewed as a diverse, dynamic and ever-changing whole which had a number of consistent characteristics that helped define it. Mochnacki was incorporated into the discourse concerning the 19th century, so in a sense on modernity as well, because the experience of modernity was what characterised the rapidly-developing civilisation of the 19th century. For Chmielowski, this modernity was personified by Hippolyte Taine, a positivist and philosopher, whose theory was supposedly predicted in one way or another by Mochnacki. The point is not about the correctness of Chmielowski’s diagnosis as it can be questioned, discussed and rejected. It is about the fact that Mochnacki, especially from the point of view of his domestic activity (before the November Uprising) could have been perceived in the 19th century and could still be today, as a literary critic and opinion journalist who was thoroughly modern in his own time.